Communication about sustainability in the food value chain : communicative challenges and opportunities - Mäehans, Astrid (SLU/Dept. of Urban and Rural Development, 2017)
A change in diets is vital due to the high environmental impact of food. To enable this change communication about sustainable food plays an important role. Food and sustainability are both areas involving a high level of complexity, making the relationship between communication, sustainability and food a central area to study. The thesis is written in connection to One Planet Food, a foodinitiative from World Wild Fund for Nature, which steered the focus of the study to communication within the food value chain. This thesis examines how actors working within the food value chain experience communicative challenges and opportunities in connection to sustainability. The Actors are interviewed though semi-standardized expert interviews to study their subjective understanding of communication in connection to sustainability. A theoretical framework is build based on Per Espen Stoknes’ model of strategic communication, which is evaluated in connection to the actor’s experiences of sustainability communication. The interviews showed patterns of both challenges and opportunities in connection to sustainability messages, and the patterns were also possible to link to parts of Stoknes’ strategies. Communication about sustainability showed to be a complex area, however concluded in that both the interviewed actors and Stoknes argued for a communication strategy of positive, simple and consensus oriented communication. Communication about sustainability showed to be limited due to aspects as an individual focused message, profit being a competing factor with sustainability, communication noise and a lack of dialogue with the audience.